Status kerentanan Ae. aegypti terhadap beberapa golongan insektisida di Provinsi Kalimantan Selatan - Nita Rahayu; Sri Sulasmi; Yuniarti Suryatinah (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2017)
Insecticide resistence study to DHF vector Aedes aegypti was carried out in Kalimantan Selatan Propince. The objective of this study was to map the insecticide susceptibility of Aedes aegypti population to the three chemical groups of insecticide used in public health, in Kalimantan Selatan. Laboratory-reared. F2 generation of field population of Aedes aegypti from nine and three Municipalities in Kalimantan Selatan Propinces were used respectively. The susceptibility test were carried qut using impregnated paper base on WHO recommended doses which are 0.8% Malathion and 0,05% cyipermethrin, 0,05% Lambdasihalotrin. The results suggested that population of Aedes aegypti collected from nine municipalities, regencies/cities in Kalimantan Selatan Propince were resistant to Malathion 0.8%, Lambdasihalotrin 0,03% and cypermethrin 0.05%, including Deltamethrin 0.025%. It is important to rotate the insecticides which are used for fogging, especially Malathion.